Internalization of Social Value Based on Character Education Strengthening through Scouting Extracurricular Activities in Public Junior High School 1 Batang - Sudiami, Dinok; Martitah, Martitah; Subagyo, Subagyo (JESS (Journal of Educational Social Studies), 2019)
Internalization of character education strengthening is very necessary to overcome the moral degradation that is occurring in the present. Brawl, drugs, low respect for young people, and lifestyle changes that lead to unhealthy behavior. This study aims to analyze the implementation of scout extracurricular activities in schools, efforts to internalize character values, and their implications for student behavior, through scout extracurricular activities. This study uses qualitative methods, with a case study approach. The subject is Kamabigus, four coaches, three subject teachers, and 30 students. Data collection techniques are participatory observation, structure, and in-depth interviews and documentation. Test validity using sources and triangulation techniques. Data analysis uses interactive analysis through data collection, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of scouting education in Curriculum 2013 included three activities, namely block, actualization, and regular. Internalization of character education strengthening is carried out through intervention, for example, habituation, mentoring, and involvement of other parties. Internalization of character education strengthening is pursued through internal programs and external programs. Internalization of character values carried out continuously that will be habituation for students. The implication is, there is a positive change in behavior, especially in the character of independence, and cooperation in every activity carried out. Crystallization of the nature of autonomy and collaboration will be beneficial for students when plunging into community life.